2008
DOI: 10.1097/olq.0b013e31817e2491
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Transmission of HIV-1 Among Serodiscordant Couples in Porto Alegre, Southern Brazil

Abstract: Heterosexual transmission occurred more frequently from HIV-infected males to females (rate ratio 3.5; CI, 95% 0.8-16.5 P = 0.259), although without statistical significance, probably because of the small sample. Transmitters showed significantly higher median viral loads (P = 0.042) suggesting that heterosexual transmission of HIV is more a function of viral load than gender of index case. ARV use may play a role in the prevention of HIV-1 heterosexual transmission. Other factors may be involved and should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 21 publications
4
50
0
2
Order By: Relevance
“…15,16 HAART reduction of maternal plasma virus load has been established as the gold standard for prevention of antepartum MTCT and potentially may prove to be highly effective in the prevention of HIV-1 sexual transmission. 17 In addition, given the immunologic properties of breast milk, it is feasible that treatment of mothers could ameliorate the immunologic characteristics of breast milk, and in this way also promote infant survival.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 HAART reduction of maternal plasma virus load has been established as the gold standard for prevention of antepartum MTCT and potentially may prove to be highly effective in the prevention of HIV-1 sexual transmission. 17 In addition, given the immunologic properties of breast milk, it is feasible that treatment of mothers could ameliorate the immunologic characteristics of breast milk, and in this way also promote infant survival.…”
Section: Discussionmentioning
confidence: 99%
“…An expanding series of ecological (Porco et al, 2004;Das et al, 2010;Montaner et al, 2010;Tanser et al, 2013), observational (Melo et al, 2008;Sullivan et al, 2009;Del Romero et al, 2010;Donnell et al, 2010;Lu et al, 2010;Jia et al, 2012), and modeling studies (Granich et al, 2009;Eaton et al, 2012), as well as the randomized controlled trial HPTN 052 (Cohen et al, 2011), has sparked enthusiasm that use of ART for prevention, in combination with other prevention and treatment interventions, could lead to an AIDS-free generation. In addition, the use of antiretroviral drugs by HIV uninfected persons who inject drugs (PWID) for prevention of acquisition of HIV infection has received attention based on the findings from a recently published randomized placebo-controlled trial of antiretroviral prophylaxis, the Bangkok Tenofovir Study, which reported a 48.9% reduction in HIV incidence (95% CI 9.6-72.2%, p = 0.01) in PWID who used daily oral tenofovir as compared to PWID assigned to placebo, both in conjunction with other risk reduction interventions (Choopanya et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Les études observationnelles Sept études observationnelles ont comparé le risque de transmission du VIH au sein de couples sérodifférents (un partenaire VIH + , l'autre VIH -) en fonction du statut ARV du partenaire VIH + [10][11][12][13][14][15][16]. Six études ont montré un impact positif des ARV sur le risque de transmission du VIH, et une étude a conclu négativement (Tableau I).…”
Section: Impact Du Tasp Au Niveau Des Couples Sérodifférentsunclassified